Being a Good Friend - Schuh, Mari C., 1975- (North Mankato, Minnesota : Pebble, a Capstone imprint, 2021)
"To have good friends, you need to be a good friend. Listen. Be kind. Be reliable. Put others first. Being a good friend takes work, but the end result is worth it!"
Lots of Friends
Includes bibliographical references (page 31) and index.
Keywords: Friendship -- Juvenile literature; Friendship in children -- Juvenile literature